The Meaning of Tax Fairness for Individual Taxpayers: A Qualitative Study on the Factors Shaping Compliance - Yoga Adi Prayogi; Ruchan Sanusi (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2025)
Tax fairness has become a central concern in improving individual taxpayer compliance in Indonesia, particularly amid increasingly complex regulations and declining public trust in fiscal institutions. This study stems from the urgent need to understand how individual taxpayers interpret the notion of tax fairness and how these interpretations shape their willingness to comply. The primary objective is to explore the underlying dimensions of tax fairness procedural, distributive, and interactional and to explain how these dimensions relate to the development of voluntary compliance. Employing an interpretive qualitative approach, this research relies on in-depth interviews with 15 individual taxpayers located in Jakarta, Yogyakarta, and Medan, selected through purposive sampling. The data were examined using Interpretative Phenomenological Analysis (IPA) to uncover recurring themes and the subjective experiences shared by participants. Findings reveal that perceptions of procedural and interactional fairness exert the strongest influence on compliance behavior, while distributive fairness is often viewed negatively due to perceived inequality in public benefit allocation and the complexity of tax rules. Trust in government and social morality emerge as critical mediators linking fairness perceptions to voluntary compliance. The study contributes theoretically by integrating Equity Theory, Tax Morale Theory, and the Slippery Slope Framework within the Indonesian cultural context, emphasizing that tax fairness forms the moral foundation of voluntary compliance. Practical implications highlight the need for equitable public services, stronger fiscal transparency, and value-based tax education. Future research is encouraged to adopt mixed-methods designs to provide deeper quantitative insights into the relationship between fairness, trust, and tax compliance across diverse social settings.